Determinants of Economic Growth in the Kedu Residency Period 2010-2019 - Luthfiana Riski Dewanti; Gentur Jalunggono (Indonesian Financial Review, 2022)
Economic growth is very important to measure economic progress as a result of national development. Several factors can be used in calculating economic growth. The purpose of this study is to analyze how the influence of Gross Regional Domestic Product (GRDP), Human Development Index (HDI) and total poor population on economic growth in the Kedu Residency. This research was conducted in districts or cities in the Kedu residency area for 10 years starting from the period 2010-2019. This study uses a fixed effect model. The analysis shows that the Gross Regional Domestic Product (GRDP) variable and the Human Development Index (HDI) together have a positive and significant effect on economic growth in the Kedu Residency. Variable of poor people has a positive and significant influence on economic growth in the Kedu Residency.